2013
DOI: 10.1155/2013/567134
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Compare the Analgesic Efficacy of Intrathecal Bupivacaine Alone with Intrathecal Bupivacaine Midazolam Combination in Patients Undergoing Elective Infraumbilical Surgery

Abstract: Spinal anaesthesia, which is one of the techniques for infraumbilical surgeries, is most commonly criticized for limited duration of postoperative analgesia. Several adjuvants have been tried along with local anesthetic for prolonging the duration of analgesia. In this study, we have observed the effect of midazolam as an adjuvant in patients undergoing infraumbilical surgery. In this prospective, randomized, double blinded, and parallel group and open label study of 90 adult patients aged 18–60 years, of Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
3
15
2
Order By: Relevance
“…Although previous studies 12,14,24 have reported a decreased incidence of PONV with the use of intrathecal midazolam, we did not find any significant difference in PONV among groups. This may be because our study was not adequately powered for PONV.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although previous studies 12,14,24 have reported a decreased incidence of PONV with the use of intrathecal midazolam, we did not find any significant difference in PONV among groups. This may be because our study was not adequately powered for PONV.…”
Section: Discussioncontrasting
confidence: 99%
“…Others also observed that intrathecal midazolam produced significant postoperative pain relief in patients undergoing lower abdominal and perineal surgeries. 12,13,15,17 Midazolam produces spinally mediated analgesia that is different in quality from that produced by the μ-opioid agonist fentanyl. The analgesic effects of intrathecal midazolam have been proposed to be due to its intrathecal spinal receptor interactions affecting the type A gamma-aminobutyric acid receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[11][12][13][14] The duration of analgesia in the test group was increased by 85 minutes in the study by Akhtaruzzaman et al and by 87 minutes in the study by Sidiq et al The study by Chattopadhyay et al was also done for lower abdominal surgeries like ours, but they used larger dose of anaesthetics (12.5 mg bupivacaine and 2 mg midazolam) and so achieved longer duration of analgesia (100 minutes) in test group compared to our study. 15 No difference in sedation levels was found in the two groups, similar to studies by Prakash et al and Shadangi et al 16,17 There was no difference between both the groups with respect to quality of anaesthesia unlike studies by Vasanthi et al and Akhtaruzzaman et al who observed better quality anaesthesia in test group. Also, incidence of side effects viz.…”
Section: Resultssupporting
confidence: 76%
“…8 The most common side effects with the use of opioids include pruritis, respiratory depression, nausea, vomiting, urine retention and sedation. 9 Various animal studies have also been conducted to confirm that Nalbuphine was not neurotoxic. Rawal et al in a sheep model showed that even large doses of 15-24 mg of napbuphine were not associated with hypertensive changes in spinal cord.…”
Section: Discussionmentioning
confidence: 99%